2006
DOI: 10.1016/j.jfms.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bartonella henselae antibodies in serum of cats with and without clinical signs of central nervous system disease

Abstract: Bartonella henselae is occasionally associated with neurological dysfunction in people and some experimentally infected cats. The purpose of this study was to determine whether B henselae seroprevalence or titer magnitude varies among cats with neurological disease, cats with non-neurological diseases, and healthy cats while controlling for age and flea exposure. There was no difference in B henselae seroprevalence rates between cats with seizures and cats with other neurological diseases. Cats with non-neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…seropositive rates were higher in healthy control group cats than in cats with uveitis or neurologic disease. 36,37 However, based on the results of this study, testing for bartonellosis as described above may be warranted in cats with unexplained hyperglobulinemia, particularly if clinical findings previously associated with bartonellosis and exposure to C. felis are present.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…seropositive rates were higher in healthy control group cats than in cats with uveitis or neurologic disease. 36,37 However, based on the results of this study, testing for bartonellosis as described above may be warranted in cats with unexplained hyperglobulinemia, particularly if clinical findings previously associated with bartonellosis and exposure to C. felis are present.…”
Section: Discussionmentioning
confidence: 92%
“…in this study (40%) was consistent with results from previous reports. 1,9,14,19,24,25,30,[33][34][35][36][37][38] Results of this study demonstrated a strong positive correlation between seropositivity with Bartonella spp. and hyperglobulinemia in this population of privately owned cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an initial study involving cats with seizures ( n =63) and cats with other neurologic diseases ( n =82), there was no difference in B. henselae seroprevalence rates between cats with seizures and cats with other neurologic diseases when compared with cats with nonneurologic illness ( n =163) or compared with a healthy cat population ( n =97) 81 . Seroprevalence rates were very high in all 3 groups, including seroreactivity in 50% of the cats with neurologic disease, 64% of cats with nonneurologic illnesses, and 70% of the healthy cat population 81 . In a subsequent retrospective study of 100 client‐owned cats with neurologic disease, serum and CSF were assayed for Bartonella spp.…”
Section: Feline Bartonellosismentioning
confidence: 97%
“…21,23 In naturally infected cats, Bartonella can rarely cause endocarditis and myocarditis. [26][27][28][29][30][31][32][33][34][35][36][37][38] These include uveitis, 30-32 caudal gingivostomatitis, 32-37 fever of unknown origin, 38 lower urinary tract disease, 32,36,39 chronic kidney disease, 32,36 pancreatitis, 40 lymphadenopathy ( Figure 52-2), 37 neurologic disease, 32,41,42 pododermatitis, 43 and chronic idiopathic rhinosinusitis. B. henselae DNA has been amplified from aortic valvular vegetative lesions of cats, with visualization of the organism in lesions using silver stains.…”
Section: Clinical Manifestations In Catsmentioning
confidence: 99%